The Dynamics of the Islamic Association (Persis) Educational Institutions, 1923-1962 - Rosmawati, Rosmawati; Ansori, M Afif; Andari, An An; Sugianto, Sugianto; Sudarningsih, Sudarningsih (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This study aims to elucidate Persis's pivotal role in fostering the growth of Islamic boarding school institutions in Indonesia between 1923 and 1962. Employing a descriptive qualitative approach, this research utilizes library research methods and content analysis. Primary sources include the Sipatahoenan Newspaper and Bendera Islam. The findings reveal that Persis's emphasis on primary and secondary education has culminated in the establishment of 230 Islamic Unity Islamic Boarding Schools nationwide. Moreover, Persis has notably founded the Islamic Education University as a tertiary-level institution. The organization also facilitates courses and discussion forums addressing religious matters and disseminates literature to advance the discourse on Islamic propagation and education renewal. Regarding the educational curriculum, Persis integrates Islamic studies, Quranic teachings, and Hadith studies with conventional education. However, challenges persist in the operational aspects of Islamic educational institutions, necessitating enhancements in management practices, augmenting educational facilities, and bolstering the quality of human resources.